Experience with cyclophosphamide in the treatment of a young woman with refractory dermatomyositis - Setiyohadi, Bambang; Sinto, R (Indonesian Rheumatology Association, 2011)
Dermatomyositis is an idiopathic inflammatory myopathy characterized by the presence of rash and moderate-to-severe muscle weakness secondary to inflammation of the muscle. It can be a difficult condition to treat. Systemic corticosteroids are the first choice of treatment. However, about a quarter of patients either fail to respond to steroids or develop steroid-related toxicity. Second-line agents such as azathioprine and methotrexate are then added either alone, or in combination with corticosteroids. Failure of the disease to respond tosecond-line agents can then be a problem and this is often referred to as ârefractory dermatomyositisâ. Unfortunately, there is neither agreement nor wellestablished guidelines on the best regimen or combination of immunosuppressive agents in the case of refractory dermatomyositis.